Pengaruh musik pengiring kerja terhadap kebosanan dan kelelahankerja di Tunas Asri Keramik Yogyakarta=The Effect ofBacksound Music on Work Boredom and Tiredness at Tunas Asri Keratnik Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Monotonous and repetitive works result in work boredom and tiredness and may cause work accident and lower productivity. Therefore it needs control and backsound music in the work area. This study was aimed to find out the effectiveness of backsound music to reduce boredom and tiredness. This was a pre-test and post-test group design experimental study by measuring and observing the subjects before and after treatment of backsound music on work. The equipment for measurement includes boredom questionnaires, reaction timer, luxmeter, heat stress apparatus, sound level meter, metronome, tape recorder, amplifier, speaker and respondent forms. The results of analysis using t-test and measurement of effectiveness of backsound music on work to decrease boredom and tiredness using square omega estimation. T-test of boredom before and after treatment snowed significant result with p=0.000 (p